Paraspinal muscle volume and fatty infiltration after circumferential minimally-invasive deformity correction - John Paul G. Kolcun; Ryan M. Kelly; Bradley L. Kolb; Dustin H. Kim; Alireza Borghei; John E. O'Toole; Richard G. Fessler (World Neurosurgery: X)
Introduction: Paraspinal muscle robustness is an area of growing interest in spinal deformity that may impact biomechanical integrity and patient quality-of-life after reconstructive surgery. Changes in paraspinal musculature after circumferential minimally-invasive (cMIS) deformity correction have not yet been investigated. Methods: We identified patients who underwent cMIS deformity correction and had lumbar spine MRIs at baseline and at minimum 1-year postoperatively. Using T2-weighted MRI, we measured total muscular volume of the psoas major, erector spinae, and multifidus muscles. We used the threshold method to determine fatty infiltration as percent fat area (PFA) along the length of these scanned regions, encompassing the final surgical construct. Results: We identified 10 patients who met inclusion criteria. On average, patients underwent interbody fusion at 3.8 ± 0.9 disc levels and posterior instrumentation at 4.6 ± 1.7 vertebral levels. All constructs included lateral interbody fusion (average 2.7 ± 0.8 levels); 6 were from a right-sided approach. Postoperative MRIs were obtained at 28 ± 14.2 months.There were no significant changes in pre- and postoperative volumes or PFA in any muscle group. There were no significant differences in left/right psoas volume or PFA in patients when stratified by side of lateral approach, nor did the number of lateral interbody fusion levels correlate with psoas volume or PFA. Change in posterior paraspinal musculature characteristics did not correlate with increasing number of fixated levels, nor significantly differ in patients who underwent posterior decompression. Preoperative muscle volumes were strongly correlated with postoperative volumes. Conclusions: In this pilot series, paraspinal and psoas muscle volumes were preserved after circumferential MIS deformity correction. Fatty infiltration was not increased in paraspinal muscles after multi-level percutaneous instrumentation, nor in the psoas after multi-level trans-psoas approaches. These findings call for more in-depth investigation in a larger cohort of patients with comparison to open deformity correction patients to determine the impact of muscle volume changes on clinical outcomes.